Circulating biomarkers of left ventricular hypertrophy in pediatric coarctation of the aorta. (16th January 2019) - Frank, Benjamin S.; Urban, Tracy T.; Lewis, Karlise; Tong, Suhong; Cassidy, Courtney; Mitchell, Max B.; Nichols, Christopher S.; Davidson, Jesse A.
Abstract: Objective: Patients undergoing surgical repair of aortic coarctation have a 50% risk of pathologic left ventricular remodeling (increased left ventricular mass or relative wall thickness). Endothelin 1, ST2, galectin 3, norepinephrine and B‐natriuretic peptide are biomarkers that have been associated with pathologic LV change in adult populations but their predictive value following pediatric coarctation repair are not known. Hypothesis: Biomarker levels at coarctation repair will predict persistent left ventricular remodeling at 1‐year follow up. Design: Prospective, cohort study of 27 patients' age 2 days‐12 years with coarctation of the aorta undergoing surgical repair. Echocardiograms were performed preoperation, postoperation, and at 1‐year follow‐up. Plasma biomarker levels were measured at the peri‐operative time points. Association between biomarker concentrations and echocardiographic parameters was assessed. Results: Neither left ventricular mass index nor relative wall thickness varied from pre‐op to post‐op. At pre‐op, relative wall thickness was elevated in 52% and left ventricular mass index was elevated in 22%; at follow‐up, relative wall thickness was elevated in 13% and left ventricular mass index was elevated in 8%. Presence of residual coarctation did not predict left ventricular remodeling (AUC 0.59; P  > .05). Multivariable receiver operating characteristic curve combining pre‐op ST2 and endothelin 1 demonstrated significant predictive ability for late pathologic left ventricular remodeling (AUC 0.85; P  = .02). Conclusions: Persistent left ventricular hypertrophy and abnormal relative wall thickness at intermediate‐term follow‐up was rare compared to previous studies. A model combining pre‐op endothelin 1 and ST2 level demonstrated reasonable accuracy at predicting persistent abnormalities in this cohort. Larger studies will be needed to validate this finding and further explore the mechanism of persistent left ventricular remodeling in this population.